Factors determining satisfaction among facility-based maternity clients in Nepal - Suresh Mehata; Yuba Raj Paudel; Maureen Dariang; Krishna Kumar Aryal; Susan Paudel; Ranju Mehta; Stuart King; Sarah Barnett (BMC, 2017)
Abstract Background With an increasing number of institutional deliveries, the Nepalese health system faces a challenge to ensure a quality of service provision. This paper aims to identify the determinants of client satisfaction with maternity care in Nepal using data from a nationally representative health facility survey. Methods A total of 447 exit interviews, with women who had either recently delivered or who had experienced obstetric complications, were conducted across 13 districts in Nepal (87% in hospitals, 8% in Primary Health Care Centres (PHCCs), and 5% in Sub/Health Posts(S/HPs). Client satisfaction was measured using an eight item scale that covered accessibility, interpersonal communication, physical environment, technical aspect of care and decision making. A client satisfaction index was computed using ordinal principal component analysis. A multivariate probit model was used to assess the net effect of explanatory variables on client satisfaction. Results Longer waiting times and overcrowding increased the likelihood of dissatisfaction. Having an opportunity to ask questions was positively associated with client satisfaction. Respondents from hill districts and rural areas were more likely to be satisfied in comparison to respondents from mountain, terai and urban areas. Socio-demographic factors (age, parity, caste/ethnicity, education, and ecological zone) and supply side factors (the time taken to reach a facility, type of facility, payment for services, and unknown heath worker or anyone entering the delivery room) were not statistically associated with satisfaction. Conclusions The findings suggest client satisfaction with the quality of maternity services in Nepal could be improved by reducing waiting times and overcrowding, and giving the mothers adequate time to ask questions. If clients are more satisfied they are more likely to use the facility again/recommend to a friend.